Strategy Proof Mechanism for Bike-Sharing Maintenance Accomplishment Probability - LI Lianxin, SHI Bing, YUAN Han (Jisuanji kexue yu tansuo, 2022)
As a green and low-carbon transportation way, bike-sharing provides lots of convenience in our daily life. However, the daily usage of sharing bike may result in some maintenance problems, such as bicycle dispatching to the specific destinations. The bike-sharing platform hires and pays to users in order to excite them to accomplish maintenance tasks. However, there are multiple users competing for the maintenance tasks, and they may strategi-cally report their task accomplishment probability in order to make more profits, which may result in inefficient task dispatching for the platform. In more detail, regarding users’ strategic behavior about reporting task accomplish-ment probability, this paper designs a strategy proof mechanism to ensure that the task accomplishment probability satisfies a certain threshold, and achieves the goal of minimizing the task accomplishment cost. The mechanism consists of a task dispatching algorithm and a user pricing algorithm. The task dispatching algorithm is based on a greedy method. The user pricing algorithm is based on Myerson’s themes. It is theoretically proven that the proposed mechanism can satisfy the properties of incentive compatible and individual rationality. Furthermore, the proposed mechanism is evaluated based on Mobike dataset in terms of task accomplishment cost, user average expected utility and user expected utility probability density. The results show that, compared with the VCG (Vickrey-Clarke-Groves) mechanism, the proposed mechanism can achieve a constant times of the approximate ratio, lower task accomplishment cost and a higher average expected utility for users. Moreover, it can prevent users’ strategic behavior in task accom-plishment probability.